History on organotin compounds, from snails to humans - Sousa, Ana C. A.
Organotin compounds are industrial chemicals used as biocides, polyvinyl chloride stabilizers and industrial catalysts for the manufacture of silicone and polyurethane foams. Despite multiple applications, organotin notoriety is due to tributyltin, a potent biocide used in antifouling paints. Because of the intensive use of tributyltin for the protection of ships’ hulls, tributyltin has been largely released into waters, resulting in adverse and even bizarre effects on aquatic organisms, such as imposex in gastropods. However, organotins include other compounds such as tributyltin derivatives, phenyltins and octyltins. Organotin use in plastics, silicone and foams results in their occurrence almost everywhere, e.g., clothes, toys, wallpaper, food containers, household piping and medical devices. Hence, humans are exposed to organotins not solely through ingestion of contaminated seafood but also through direct contact with treated products and by inhalation and ingestion of dust. As a consequence, organotins have been detected in human samples. Toxicity data reveal that organotins are endocrine disruptors, immunotoxicants, carcinogens and obesogens. Here, we review the levels, fate and effects of organotin compounds toward wildlife and humans, starting with a description of organotin applications, with particular incidence in antifouling paints. The global contamination of the marine environment and the deleterious effects of tributyltin onto nontarget organisms are addressed, with particular attention to the imposex phenomenon. The restrictions on tributyltin use in antifouling paints are also described alongside with the new regulations for organotins in consumer products. The sources and pathways of organotins in the environment are discussed, studies in human exposure are presented, and future research is proposed.